Coinfection of Mycobacterial diseases (Community Based Medical Journal, 2021)
Although both mycobacterial infections are endemic in developing countries, the coinfection has hardly been reported in the last decade. The combined National TB & Leprosy Control Programme of Bangladesh came into effect in 1994. Though the Elimination of Leprosy (